Evaluating the Fibroblast Growth Factor-23 and Phosphate in Iraqi Patients with Acromegaly (Baghdad Science Journal, 2024)
Fibroblast growth factors-23 (FGF-23) are a class of cell signaling proteins produced by macrophages. They have a range of roles, but they play a particularly important role in the development of animal cells, where they are essential for appropriate growth. Phosphate, which is found in the body as both organic and mineral phosphate, plays crucial roles in cell structure, communication, and metabolism. Most phosphate in the body resides in bone, teeth, and inside cells, with less than 1% circulating in serum. The aim of the study is to evaluate the levels of the Fibroblast Growth Factors-23 and phosphate and receiver operating characteristic (ROC) in acromegaly patients against healthy control. A case control study Fibroblast Growth Factors-23, Phosphate, Growth hormone and Insulin like growth factor-1 were carried out by recruiting 61 acromegalic patients who were enrolled in the study plus 60 control group. The results showed significant higher values in Fibroblast Growth Factors-23 and Phosphate levels in acromegalic patients than healthy control group whereas the Mean±S.D was (3627.49±395.77, 1809.94±159.63) and (1.44±0.58, 0.59±0.26) and we found the Fibroblast Growth Factors-23 was high in control group among men versus women (1866.81±177.86, 1756.98±121.07) and (P value 0.009). According to the current study, patients with acromegaly have high significant Fibroblast Growth Factors-23 and phosphate levels than the healthy control group and they are the most specific and sensitive marker in acromegalic patients in a term of defining and excluding the disease